Pilomyxoid astrocytoma of the pineal region: Cytopathological features and differential diagnostic considerations by intraoperative smear preparation. Issue 2 (28th February 2014) - Hayashi, Toshitetsu; Haba, Reiji; Kushida, Yoshio; Katsuki, Naomi; Shibuya, Shinsuke; Kadota, Kyuichi; Matsunaga, Toru; Miyake, Keisuke; Tamiya, Takashi
<x xml:space="preserve">Abstract</x> Pilomyxoid astrocytoma (PMA) is a recently identified type of pilocytic astrocytoma (PA) with shorter progression‐free and overall survival, higher rate of recurrence, and higher risk of leptomeningeal spread compared to pilocytic tumors (WHO grade 2 designation). A case is presented here in which intraoperative imprint smears of a pineal region tumor in a 14‐year‐old girl revealed cytologic monomorphism, elongated cells with bland nuclei embedded in a myxoid background. The tumor cells possessed uniformly round nuclei with a smooth nuclear outline, fine granular chromatin, and small nucleoli. Slender cytoplasmic fibrillary processes and angiocentric arrangement were observed but Rosenthal fibers or eosinophilic granular bodies were absent. A cytologic diagnosis of PMA of the pineal region was suggested by intraoperative smear preparation. Histology and immunohistochemical results confirmed the final diagnosis. This report shows that smear preparation can be trustworthy for the intraoperative diagnosis of PMA, helping to determine the appropriate neurosurgical procedure and therapeutic implications. Diagn. Cytopathol. 2015;43:121–124. © 2014 Wiley Periodicals, Inc.